Jumayeva, Leyla - (:unkn) unknown (My University, 2026)
Leyla Arif Jumayeva, PhD in Philology, is a Lecturer at the Department of Foreign Languages, Azerbaijan University of Architecture and Construction. She received her Bachelor's and Master's degrees in Philology from Azerbaijan University of Languages and earned her PhD in Germanic Languages in 2025. Her research focuses on English language teaching, applied and cognitive linguistics, English for Specific Purposes (ESP), academic communication, conceptual integration, artificial intelligence in language education, and innovative teaching technologies. She is the author of a monograph, a curriculum programme, and numerous conference papers and is currently preparing two textbooks. Before joining AzUAC in 2023, she taught at Azerbaijan University of Languages, Khazar University, and the Azerbaijan State University of Economics (UNEC). She has participated in international academic and professional development programmes in the United Kingdom, Turkey, and China and actively contributes to the organization of international conferences and academic events at AzUAC.